The genomic origins of the world's first farmers - Marchi, Nina; Winkelbach, Laura; Schulz, Ilektra; Brami, Maxime; Hofmanová, Zuzana; Blöcher, Jens; Reyna-Blanco, Carlos S; Diekmann, Yoan; Thiéry, Alexandre; Kapopoulou, Adamandia; Link, Vivian; Piuz, Valérie; et al. (Cell, 2022)
The precise genetic origins of the first Neolithic farming populations in Europe and Southwest Asia, as well as the processes and the timing of their differentiation, remain largely unknown. Demogenomic modeling of high-quality ancient genomes reveals that the early farmers of Anatolia and Europe emerged from a multiphase mixing of a Southwest Asian population with a strongly bottlenecked western hunter-gatherer population after the last glacial maximum. Moreover, the ancestors of the first farmers of Europe and Anatolia went through a period of extreme genetic drift during their westward range expansion, contributing highly to their genetic distinctiveness. This modeling elucidates the demographic processes at the root of the Neolithic transition and leads to a spatial interpretation of the population history of Southwest Asia and Europe during the late Pleistocene and early Holocene.
Keywords: Neolithic transition; Evropa; genomika; Europe; History, Ancient; demographic processes; genetický drift; mitochondriální DNA; Genomics; Humans; ancient genomics; demographic inference; demogenomic modeling; zemědělství; Agriculture; Human Migration; genom; human evolution; Genetic Drift; DNA, Mitochondrial; Farmers; population admixture; zemědělci; upper Palaeolithic; lidé; migrace lidstva; dějiny starověku; Genome